Colvin R de Silva : selected speeches & writings - De Silva, Colvin R.; De Silva, Colvin R.; Muthiah, Wesley S.; Wanasinghe, Sydney (Colombo : Young Socialist Publications, 2007)
Chiefly on political conditions of Sri Lanka; includes articles on socialism; covers the period, 1935-1989; published on the occasion of the hundredth birth anniversary of De Silva.
Keywords: Socialism -- Sri Lanka -- History; Sri Lanka -- Politics and government